Social support and job satisfaction in nursing staff: understanding the link through role ambiguity - Orgambídez, Alejandro (2022)
Aim This study aimed to analyse the mediator effect of role ambiguity between social support from supervisor and colleagues and job satisfaction in Portuguese nursing staff. Background Few studies have analysed the processes through which social support increases job satisfaction in the nursing context. Design A cross-sectional design using questionnaires. Method A total of 124 registered nurses and 130 certified nursing assistants participated in the study. Mediation analysis was performed by calculating percentile confidence intervals (10,000 resamples). Results Mediation analysis revealed a partial mediation between social support and job satisfaction through role ambiguity. The direct effect was greater in the case of supervisor support. Conclusions Social support is a crucial resource in the nursing work context with a beneficial effect on well-being (e.g. reducing role stress) and job satisfaction. Implications for Nursing Management Managers of hospitals and health units can establish the organizational bases to facilitate this process, considering the importance of the role of the supervisors and colleagues in the provision of high levels of instrumental and socio-emotional support.